Gerontological nursing : competencies for care - Mauk, Kristen L. (Burlington, MA : Jone and Bartlett Learning, 2018)
"Gerontological Nursing: Competencies for Care, Fourth Edition focuses on caring for the elderly by employing a holistic and interdisciplinary approach. The text follows the framework of the core competencies for baccalaureate nursing education published by the American Association of Colleges of Nursing (AACN) and the John A. Hartford Foundation Institute for Geriatric Nursing. This framework is structured to ensure nursing students attain the recommended knowledge to achieve the competencies necessary to provide excellent care to older adults."--Back cover
ntroduction to gerontological nursing -- The aging population -- Theories of aging -- Review of the aging physiological system -- Teaching and communication with older adults and their families -- Comprehensive assessment of the older adult -- Promoting healthy aging, independence, and quality of life -- Identifying and preventing common risk factors in the elderly -- Management of common illnesses, diseases, and health conditions -- Nursing management of dementia -- Polypharmacy -- Falls in older adults -- Delirium -- Anxiety and depression in the older adult -- Urinary incontinence -- Sleep disorders -- Dysphagia and malnutrition -- Pressure ulcers -- The gerontological nurse as manager and leader within the interprofessional team -- Ethical and legal principles and issues -- Technology and care of older adults -- Culture and spirituality -- Sexuality -- Elder abuse and mistreatment -- Pain management and alternative health modalities -- Disaster preparation, response, and recovery -- End-of-life care -- Care transitions, system models, and health policy in aging --
Includes index.
Keywords: GERIATRIC NURSING -- METHODS